Opportunities and Challenges of Poverty Alleviation and Independence of The Kubu Tribe Community in Merangin Regency - Lukman Lukman (Indonesian Economic Review, 2023)
There are two main purposes of this study. First, this research aims to analyze the strengths, weaknesses, opportunities, and challenges of poverty alleviation and underdevelopment. Second, this paper analyzes the right strategies for poverty alleviation and underdevelopment of the Kubu Tribe. Data collection used questionnaires to respondents from the Kubu Tribe community groups. Data analysis used is SWOT analysis through a series of internal factor analysis strategy (IFAS) calculations, external factor analysis strategy (EFAS), and strategy factor analysis strategy (SFAS) by taking into account the weight and rating values. Which is then formulated into a Tows matrix table. The results of the SFAS strategy that are right for poverty alleviation and underdevelopment are the SO (strength opportunities) strategy which occupies the highest score of 3.557 which is in position I, with the Rapid Growth Strategy, increasing coaching activities, counseling, and providing appropriate skills training and maximizing all opportunities and stability. Growth Strategy, namely maintaining existing progress.